2020
DOI: 10.1080/14992027.2020.1851401
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of face coverings on communication: an indirect impact of COVID-19

Abstract: Objective: To understand the impact of face coverings on hearing and communication. Design: An online survey consisting of closed-set and open-ended questions distributed within the UK to gain insights into experiences of interactions involving face coverings, and of the impact of face coverings on communication. Sample: Four hundred and sixty members of the general public were recruited via snowball sampling. People with hearing loss were intentionally oversampled to more thoroughly assess the effect of face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
178
2
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(200 citation statements)
references
References 38 publications
11
178
2
9
Order By: Relevance
“…In June 2020, the World Health Organization warned about the potential risks and harms of face masks on daily communications. As evidenced by this study, when a talker wears a face mask the listening effort increases, while performance and confidence in what we listen decrease (see also Coniam, 2005;Llamas et al, 2009;Saunders et al, 2020). This could potentially result in stress and misunderstandings during communications, and even lead to risky behaviors, such as pulling down face masks or reducing social distancing while trying to understand each other better.…”
Section: Discussionmentioning
confidence: 66%
“…In June 2020, the World Health Organization warned about the potential risks and harms of face masks on daily communications. As evidenced by this study, when a talker wears a face mask the listening effort increases, while performance and confidence in what we listen decrease (see also Coniam, 2005;Llamas et al, 2009;Saunders et al, 2020). This could potentially result in stress and misunderstandings during communications, and even lead to risky behaviors, such as pulling down face masks or reducing social distancing while trying to understand each other better.…”
Section: Discussionmentioning
confidence: 66%
“…Last, masked interactions might be regarded as more ambiguous if individuals believe that masks may alter or diminish the intensity or intelligibility of one's speech, resulting in audibly-impaired social interactions. Although much of the current research indicates that masks have relatively little influence on the intelligibility of speech for people with normal hearing (Saunders et al, 2020), it is possible that individuals with SA may nonetheless perceive them as a communication barrier. Indeed, Howard (2020) found that a small minority (4%) of individuals cited concerns related to the ease of interacting while wearing a mask as a reason for not wearing one during the coronavirus pandemic.…”
Section: Masks As a Barrier To The Interpretation Of Social And Emotional Feedbackmentioning
confidence: 82%
“…Furthermore, in the long run, wearing the mask in some subjects could induce the need to increase the vocal effort in order to make up both for the reduction of intensity of the voice and for the lack of the normal and important nonverbal language (kinetic facial expression) that contributes to communication. 20,21 Vocal effort manifests as a series of changes to the voice signal, including those that can be quantified by amplitude-, time-, and spectral-based measures. 22 Effortful voice production is a critical component of voice disorders and is considered to be a component of vocal hyperfunction.…”
Section: Discussionmentioning
confidence: 99%